Ethno-psychiatry and folklore psychiatry - Seguin, Carlos Alberto (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
On several occasions, in Congresses and through publications, I have tried to define folklore psychiatry and to delimit its field with the goal of initiating authentic interest then what I consider an important and neglected aspect of modern psychiatry.